Diagnosis and management of Canine Renal Cell Carcinoma with special reference to Shear Wave Elastography - Jena, B; Mohindroo, J; Anand, A; Gupta, K (Journal of the Hellenic Veterinary Medical Society, 2024)
This report focuses on the diagnosis and surgical management of unilateral renal cell carcinoma in a 7-year-old male intact German Shepherd dog. The dog was presented with fever, haematuria, inappetence, infrequent bouts of emesis, and progressive weight loss. Palpation revealed a hard, round mass in the right cranial abdomen. A presumptive diagnosis of unilateral renal neoplasm was made based on clinical signs, haematobiochemical analysis, and radiography. B-mode ultrasound examination demonstrated an enlarged right kidney extending up to the ventral midline. The kidney exhibited heterogenous echotexture, loss of renal architecture, and only a small healthy portion at the caudal pole. Point Shear Wave Elastography analysis revealed elevated values both in terms Shear Wave Velocity (m/sec) and Young’s Modulus Stiffness Value (kPa), indicating the presence of renal malignancy. To treat the condition, unilateral nephroureterectomy was performed under general anaesthesia. Histopathological examination confirmed the diagnosis of renal cell carcinoma. Consequently, it can be concluded that B-mode ultrasonography, Point Shear Wave Elastography, and nephroureterectomy played crucial roles in the successful diagnosis and surgical management of unilateral renal cell carcinoma.